Post-Divorce Child’s Nafaqah Māḍiyah: An Analysis of the Shifting from Fulfilment to the Assertion of Ownership Rights - Firdaus Firdaus; Ismail Ismail; Busyro Busyro; Endri Yenti; Mohd Nasran Mohamad (Al-Ahkam, 2023)
The claim for child’s nafaqah māḍiyah (past income) is often overlooked in the rulings of the Religious Court. This research aims to propose a shifting from the concept of li al-intifā’ (benefit) to li al-tamlīk (ownership) regarding child’s living costs claims in the Religious Court, employing the istihsān (juristic preference) approach. The objective is to ensure a more equitable judgment for the child. This study was conducted as a literature review using a normative juridical approach. The research findings reveal that the legal standpoint, which rejects any claim for child’s nafaqah māḍiyah in the Religious Court based on the argument that child’s living costs is categorized as li al-intifā’, contradicts Islamic legal principles regarding child’s living costs and fails to fulfill the principles of justice, as well as being incongruent with several other legislative provisions related to child protection. Therefore, this article proposes a shifting from the concept of li al-intifā’ to li al-tamlīk in determining child’s nafaqah māḍiyah in the Religious Court.